Kinetic Studies on Cure Kinetics of DGEBA (Diglycidyl Ether of Bisphenol-A) with Terephthalamide Hardening System generated from PET waste - Dutt, Krishna; Soni, R.K.; Teotia, Meenu; Sharma, S.P.; Singh, Harjeet (Journal of Research Updates in Polymer Science, 2013)
An aromatic amide system for epoxy resin based on diglycidyl ether of Bisphenol-A was developed through ammonolysis of PET waste. The ammonolysis of PET waste was carried out at ambient conditions of temperature & pressure. The end product, characterized as terephthalamide was used as hardener in epoxy resin (Diglycidal ether of Bisphenol-A) and triethylamine and sodium hydroxide were used as catalysts. Several samples were used to study the curing kinetics having varying amounts of the catalysts by means of Differential scanning calorimetry (DSC). Isothermal and Dynamic DSC characterization of the formulations were performed. The curing kinetics of terephthalamide with epoxy resin shows high energy of activation as 50.18 KJ/mole in the absence of catalyst which was lowered towards negative values in their presence. The optimum curing of epoxy resin heated with aromatic hardener can be obtained in 28 minutes at 320 ˚C. The use of catalysts reduced the curing time to 2.0 minutes at 60 ˚C.